All Days 2012
DOI: 10.2118/151777-ms
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Interaction with Montmorillonite Clay

Abstract: Clay swelling has been recognized as one of the main mechanisms of formation damage during various well operations. Many researchers have extensively investigated the effects of many parameters such as pH, and salinity of water-based fluids on montmorillonite swelling behavior. However, studies of supercritical carbon dioxide (CO2) interactions with montmorillonite clay have been limited. These interactions can affect injectivity during enhanced oil recovery (EOR) operations. Therefore, the main objective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Compared with water, CO 2 can induce much less swelling of clay minerals and the swelling effect is greatly dependent on the initial water content in clay minerals. For example, the experimental studies conducted by Al Otaibi et al [93] and Giesting et al [94] showed that super-critical CO 2 adsorption into clay minerals (Na or Ca-montmorillonite in this case) does not produce any significant swelling in dry clay minerals. Maximum expansion caused by CO 2 from 11.3 Å to 12.3 Å occurred when small amounts of water present in montmorillonite and the swelling is nearly an order of magnitude lower than that caused by water [94,95].…”
Section: Avoidance Of Swelling-related Issuesmentioning
confidence: 83%
See 1 more Smart Citation
“…Compared with water, CO 2 can induce much less swelling of clay minerals and the swelling effect is greatly dependent on the initial water content in clay minerals. For example, the experimental studies conducted by Al Otaibi et al [93] and Giesting et al [94] showed that super-critical CO 2 adsorption into clay minerals (Na or Ca-montmorillonite in this case) does not produce any significant swelling in dry clay minerals. Maximum expansion caused by CO 2 from 11.3 Å to 12.3 Å occurred when small amounts of water present in montmorillonite and the swelling is nearly an order of magnitude lower than that caused by water [94,95].…”
Section: Avoidance Of Swelling-related Issuesmentioning
confidence: 83%
“…While for clay minerals with high water saturation, the dehydration effect caused by CO 2 dominates the hydration effect and CO 2 also causes the net drying of clay particles, resulting in reduction of the basal spacing of swelled clay minerals. The D-spacing of Na-Montmorillonite with 64% water saturation collapsed by 15% after exposed to super-critical CO 2 [95] and Al Otaibi et al [93] found that the D-spacing of fully hydrated Na and Ca-montmorillonite decreased by a significant amount (around 25% and 14.2%) after super-critical CO 2 treatment.…”
Section: Avoidance Of Swelling-related Issuesmentioning
confidence: 99%